2022
DOI: 10.1007/s44246-022-00022-4
|View full text |Cite
|
Sign up to set email alerts
|

Analytical methods, molecular structures and biogeochemical behaviors of dissolved black carbon

Abstract: Dissolved black carbon (DBC) is one of the most active fractions in the black carbon (BC) continuum and plays a significant role in the global dissolved organic matter (DOM) pool. Connecting the BC pool between territorial and marine environments, the biogeochemical processes of DBC are significant for many aspects of aquatic chemistry. Once entering the aquatic environment, DBC will undergo degradation and exert continuing effects on water ecology. DBC can change the migration and transport of pollutants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 150 publications
0
13
0
Order By: Relevance
“…Generally, most studies have investigated the correlation between wildfires and riverine DOM/DBC over an extended period, occurring several months or years after the wildfires took place. , Environmental drivers, especially hydrology during rain and storm events are recognized as significant factors determining the postfire export of DOC and DBC. ,,, However, in scenarios where there is no rainfall, the immediate impacts of wildfires on aquatic DOM and DBC within a few days postfire remain poorly understood. Apart from soil infiltration and surface runoff, the atmosphere dry deposition of aerosols is recognized as another significant source of DBC in watersheds. ,, Therefore, it is reasonable to assume that wildfires can have immediate impacts on riverine DOM/DBC via atmospheric deposition of ash.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, most studies have investigated the correlation between wildfires and riverine DOM/DBC over an extended period, occurring several months or years after the wildfires took place. , Environmental drivers, especially hydrology during rain and storm events are recognized as significant factors determining the postfire export of DOC and DBC. ,,, However, in scenarios where there is no rainfall, the immediate impacts of wildfires on aquatic DOM and DBC within a few days postfire remain poorly understood. Apart from soil infiltration and surface runoff, the atmosphere dry deposition of aerosols is recognized as another significant source of DBC in watersheds. ,, Therefore, it is reasonable to assume that wildfires can have immediate impacts on riverine DOM/DBC via atmospheric deposition of ash.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that up to ∼90% of the terrestrially derived BC is deposited and buried in continental shelf sediments, which cover only approximately 10% of the global ocean area . The results from many studies indicate that the contents of BC buried in river-influenced coastal sediments are usually much higher than those in river-unaffected areas. In recent studies, dissolved BC (DBC) transported by rivers has received substantial amounts of attention. ,,, It is estimated that 18 ± 4 Tg year –1 of BC is transported in the dissolved phase by rivers, accounting for 12 ± 5% of the global flux of riverine-dissolved organic carbon (DOC). , In our recent study, we found that large Chinese rivers transport significant amounts of DBC and that this DBC is unlikely to be refractory in nature and could be decomposed by bacteria, which suggest a possible mechanism for the phase transformation and cycling of BC in natural systems. Although many studies have investigated BC in large rivers and in the coastal sediments of China in recent years, ,, the fate of BC transformation and cycling in marine sediments has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…25−28 In recent studies, dissolved BC (DBC) transported by rivers has received substantial amounts of attention. 3,16,29,30 It is estimated that 18 ± 4 Tg year −1 of BC is transported in the dissolved phase by rivers, accounting for 12 ± 5% of the global flux of riverinedissolved organic carbon (DOC). 12,19 In our recent study, we found that large Chinese rivers transport significant amounts of DBC and that this DBC is unlikely to be refractory in nature and could be decomposed by bacteria, 29 which suggest a possible mechanism for the phase transformation and cycling of BC in natural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its aromatic structure, it is relatively resistant to biodegradation (Czimczik & Masiello, 2007) and can persist in the ocean for tens of thousands of years (Ziolkowski & Druffel, 2010). Thus, understanding the sources and influential factors is essential for predicting its future change, which has become a hot research topic in the past decade (Bao et al., 2017; Chen et al., 2022; Dittmar, de Rezende, et al., 2012; Jaffe et al., 2013; Jones et al., 2020; Qi et al., 2020; Wagner, Brandes, et al., 2019; Yamashita et al., 2022; Ziolkowski & Druffel, 2010).…”
Section: Introductionmentioning
confidence: 99%